Auditing: Integrated Concepts and Procedures (Book). - Meyer, Philip E. (The Accounting Review, 1982)
Reviews the book "Auditing: Integrated Concepts and Procedures," 2nd ed., by Donald H. Taylor and G. William Glezen.